Hydrogen bonding and rate enhancement in the photoinduced polymerization of telechelic urethane methacrylates based on a cycloaliphatic system: tricyclodecane dimethanol - Deepak, V. D.; Rajan, J.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
A new class of telechelic urethane methacrylic crosslinkers, based on a cycloaliphatic system (tricyclodecane dimethanol and tricyclodecane monomethanol), was synthesized. The synthesis was achieved by a two-step condensation of 1,6-hexamethylene diisocyanate or isophorone diisocyanate with tricyclodecane dimethanol and capping with hydroxyethyl methacrylate. Samples of hexanediol diacrylate, tricyclodecane monomethacrylate, and tricyclodecane dimethacrylate were used as non-hydrogen-bonding monomers for comparative studies of the curing kinetics. The photopolymerization of these telechelic systems was investigated with UV irradiation in the presence of 2,2-diethoxy acetophenone as the photoinitiator, and the kinetics were followed by the monitoring of the double-bond conversion at 815 cm−1 with Fourier transform infrared spectroscopy. The hydrogen-bonded crosslinkers had higher double-bond conversions than their non-hydrogen-bonded counterparts under identical conditions. The higher cure rate could be explained by hydrogen-bonding preassociation in these systems, which brought the methacrylate double bonds within close proximity. The temperature effects on the hydrogen bonding were also investigated. A decrease in the extent of the double-bond conversion with increasing temperature was observed for the hydrogen-bonded crosslinker, in contrast to an increased conversion with temperature for hexanediol diacrylate and tricyclodecane dimethacrylate. This was directly indicative of a reduction of hydrogen bonding at elevated temperatures leading to lower conversions. © 2006 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 44: 4384–4395, 2006

Hydrogen-bonding-induced conformational change from J to H aggregate in novel highly fluorescent liquid-crystalline perylenebisimides - Jancy, B.; Asha, S. K. (Chemistry of Materials, 2008)
A series of highly fluorescent liquid-crystalline perylenebisimide molecules having amide or ester linkage and end-capped by phenyl, monododecyloxy phenyl, or tridodecyloxy phenyl units have been synthesized and fully characterized. The amide-functionalized series self-organized to form H type aggregates regardless of their end-capping in organic solvents like tetrahydrofuran (THF), toluene, and dichloromethane. On the other hand, only the monododecyloxy phenyl end-capped molecule in the ester series showed a tendency to self-organize with a typical J type aggregation in toluene. In both series, the highest aggregation tendency was shown by the one having monododecyloxy phenyl end-capping, with the transition temperature from aggregated to molecularly dissolved species occurring at 60 °C for the amide and 50 °C for the ester molecule. At higher concentrations in toluene, the fluorescence spectra of the monododecyloxy phenyl and tridodecyloxy phenyl terminal-substituted amide derivatives showed the formation of a new peak corresponding to excimer emission at 670 nm. Thin drop cast films of the perylenebisimide ester and amide series gave only excimer emission ∼670 nm upon excitation. Thermal analysis using differential scanning calorimetry (DSC), polarized light microscopy (PLM), and powder X-ray diffraction measurements were utilized to study the liquid-crystalline (LC) characteristics of the molecules. Scanning electron micrograph (SEM) of thin drop-cast samples that were annealed in toluene showed the formation of supramolecular rods several micrometers in length, especially for the amide derivatives. The ester derivative, on the other hand, showed a leaflike morphology thus differentiating it from the amide series, which have both hydrogen bonding and π−π interactions to support self-organization.

H-bonding vs non-h bonding in 100% pyrene methacrylate comb polymers:self assembly probed by tres and temperature dependent fluorescence - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
The differences in self-organization behavior in novel 100% pyrene labeled comb methacrylate polymers probed as a function of their varied origins of excimer formation are presented. The different structural variations in the polymers included the presence or absence of hydrogen bonding interactions in the form of urethane linkages, short or long alkyl spacer segments separating the pyrene units from the polymer backbone and linear versus kinked urethane linkage. The effect of variable concentration and temperature on the chemical shift of the NH proton of the urethane linkage was probed using 1H NMR experiments conducted at temperatures varying from 25 to 70 °C at two different concentrations (2.5 and 25 mmol) in DMSO-d6 as solvent. The photophysical properties of the polymers in dilute DMF solutions were investigated by steady state emission, fluorescence decay studies, time-resolved emission spectra (TRES), and variable temperature emission studies. It was observed that the polymer poly(PBH) having a non-hydrogen-bondable ester linkage in the pendant chains formed an excimer completely via a static mechanism and the ground state aggregate species were not broken even at higher temperatures. The polymer poly(PIC) having a short hydrogen-bondable urethane linkage formed an excimer via a static as well as dynamic mechanism. The other hydrogen-bondable urethane methacrylate polymers having a linear linker poly(PHH) and kinked linker (PIHP) formed excimer mostly via a dynamic mechanism with a very small contribution from the static route. The TRES studies carried out for the polymers provided significant insight into the excimer formation mechanism in these polymers. The variable temperature fluorescence studies highlighted the differences in the H-bonded vs non-H-bonded polymer as a function of their excimer recovery upon cooling.

High-voltage non-aqueous hybrid supercapacitor based on the N2200 polymer supported over multiwalled carbon nanotubes - Wavhal, Bhaiyyasaheb Anurath; Ghosh, Meena; Sharma, Sandeep; Kurungot, Sreekumar; Asha, S. K. (Nanoscale, 2021)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, is a widely accepted non-fullerene acceptor polymer that is used prominently in the energy harvesting application due to its ease of synthesis, high electron mobility, and other desirable semiconducting properties. With its recent foray into energy storage applications, there is tremendous potential for developing composites of N2200 with carbon nanotubes (CNTs) to improve its electrical properties and extend its applicability. Here we report a facile synthesis of an N2200 composite with multiwalled carbon nanotubes (MWCNTs) following an in situ approach to include MWCNTs into the polymer matrix, improving its electrochemical performance in an organic electrolyte (1 M LiClO4/propylene carbonate). The composite material with an optimum MWCNT content exhibits prominent redox behavior delivering a specific capacity of 80 mA h g((polymer))(-1) in a standard three-electrode cell. Moreover, the N2200/MWCNT composite material showing a battery-type electrochemical signature could perform as an efficient negative electrode in a high-voltage (2.4 V) hybrid supercapacitor device comprising capacitive activated carbon as the positive electrode.

High-voltage symmetric supercapacitor electrodes via in situ synthesized multiwalled carbon nanotube-doped perylenebisimide-based donor-acceptor conjugate polymer P(PDI2OD-T2) - Wavhal, Aryan Anurath; Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Kakde, Navnath R.; Prakash, Medha; Kurungot, Sreekumar; Asha, S. K. (Journal of Physical Chemistry C, 2024)
This study presents the design and synthesis of a donor-acceptor pi-conjugated polymer composite P(PDI2OD-T2)/MWCNT tailored for high-voltage symmetric supercapacitor applications. The synthesis of P(PDI2OD-T2)/MWCNT was expedited by adopting a novel in situ polymerization technique that modifies the traditional Stille polymerization process. Incorporating approximately 33% by weight of multiwalled carbon nanotubes (MWCNT) into the polymer matrix, referred to as P-2, significantly enhances its conductivity, surface area, and porosity. These improvements in the material properties contribute to the superior electrochemical performance of the composites by promoting efficient electrolyte ion transport across the electrode-electrolyte interfaces. The symmetric supercapacitor devices fabricated with P-2 electrodes employing both liquid organic (LE-P-2||P-2) and quasi-solid-state gel (QSS- P-2||P-2) electrolytes demonstrate capacitance values of 85.4 and 84.2 F g(-1), respectively, at a current density of 0.25 A g(-1), while operating at a high-voltage window of 3.1 V. Moreover, these devices exhibit robust cycling stability, maintaining approximately 70% of their initial capacitance over 45,000 cycles with a coulombic efficiency of 96%. The successful demonstration of a quasi-solid-state symmetric supercapacitor underscores the potential of flexible energy storage solutions, as evidenced by a PMMA LiClO4 gel electrolyte prototype. This flexible device not only maintains structural integrity but also achieves an impressive power density of 18,600 W kg(-1) and an energy density of 112.4 Wh kg(-1), indicating its practical viability for real-world applications.